Uterine Rupture with Evisceration of Intestines through the Vagina during Labour. (20th December 2019) - Akpan, Ubong; Akpanika, Chinyere; Nwagbara, Victor; Asibong, Udeme; Etuk, Saturday
Abstract : Uterine rupture is a life threatening obstetric emergency and is associated with high maternal and perinatal mortality. There are some risk factors associated with uterine rupture which may include: prolonged obstructed labour, previous scarred uterus, grand-multiparity, macrosomic baby, abnormal lie, instrumental delivery, induction of labour, oxytocin stimulation and excessive uterine manipulation. Its modes of presentation have been widely reported. Here, we present a case with an unusual mode of presentation where about two-third of the small intestines protruded through the vagina following some manipulations by an unskilled birth attendant. This highlights the fact that when uterine rupture is suspected, the cord-like structure protruding per vaginum may not always be umbilical cord.